2023
DOI: 10.1002/acp.4039
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a scientific reasoning intervention for conspiracy theory beliefs

Abstract: Conspiracy theory (CT) beliefs have become an important policy‐relevant research area since the events of the COVID‐19 pandemic. Increasing interest has been directed towards strategies that might reduce people's susceptibility to conspiratorial beliefs. In this study, we examined whether encouraging a stronger orientation towards critical scientific appraisal of conspiratorial accounts could reduce CT acceptance. After completing baseline measures of COVID‐19 related beliefs and analytical and scientific reas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 73 publications
(167 reference statements)
0
4
0
Order By: Relevance
“…To the best of our knowledge, this study is the first to demonstrate the independence of reflective thinking, even beyond the context of conspiracy theories, which is academically intriguing and highlights a unique characteristic of reflective thinking. In practical terms, reflective thinking interventions have been shown to reduce conspiracy beliefs (Georgiou et al, 2023). Our study indicates that fostering reflective thinking could be effective in decreasing conspiracy beliefs, regardless of the personal factors that might contribute to such beliefs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this study is the first to demonstrate the independence of reflective thinking, even beyond the context of conspiracy theories, which is academically intriguing and highlights a unique characteristic of reflective thinking. In practical terms, reflective thinking interventions have been shown to reduce conspiracy beliefs (Georgiou et al, 2023). Our study indicates that fostering reflective thinking could be effective in decreasing conspiracy beliefs, regardless of the personal factors that might contribute to such beliefs.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the design of this study does not allow for the determination of causation. To establish causation, experimental manipulation, such as the fostering reflective thinking intervention (Georgiou et al, 2023) or longitudinal design (Heiss et al, 2021), is necessary. By implementing such approaches, researchers can draw more definitive conclusions about the causal relationships between reflective thinking and conspiracy beliefs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in contrast to some prior work, the Bad News intervention also boosted reliability of real news headlines and thus significantly improved truth discernment. Finally, Georgiou et al (2023) exposed participants to a conspiracy theory, after which participants were randomized to either a control condition or a scientific reasoning manipulation where participants listened to material that debunked the conspiracy theory in question and identified logical fallacies. Overall, the authors found that the participants who completed the scientific reasoning training were less likely to endorse conspiracy theories in comparison to the control group postintervention ( d = 0.15).…”
Section: New Insights For Countering Belief In Conspiracy Theoriesmentioning
confidence: 99%
“…Generally, CTs are produced as result of the search for an alternative explanation to the official one about historical or present phenomena, and they are based on the idea that there are hidden powers or secret manipulations to hide facts from the population (Gualda et al, 2019); explaining these events and circumstances as the malevolent acts of secret and powerful groups (Douglas et al, 2017;Douglas et al, 2019). Such theories can take several different forms, but one of the most common of these being the CTs which suggest the world is ruled by a small global elite, comprised of powerful groups, mysterious figures, or alien whose aim is to make a new world order (e.g., Swami & Coles, 2010), and to achieve this they manipulate and monitor the world, being behind of the major international events or crises (e.g., Swami et al, 2013); being the governments and some major international figures possible accomplices of these events (Georgiou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%